Benzodiazepine use and occupational injuries: a systematic review and meta-analysis. (13th November 2019) - Riccò, M; Bragazzi, N L; Mezzoiuso, A G; Balzarini, F; Garbarino, S
Abstract: Objective: To investigate whether use of benzodiazepine is associated with increased risk of occupational injuries. Methods: PubMed, Cochrane, Embase and CINAHL databases were searched. A meta-analysis was performed to calculate odds ratio (OR) and 95% confidence interval (CI) among case controls, cross-sectional studies, either questionnaire or laboratory exams based. Results: A total of 20 studies met inclusion criteria, 75% of them of low quality, involving 328, 805 occupational injuries from 9 different countries, with an estimated prevalence of benzodiazepine positivity of 5.3% (95%CI 4.2-6.3), significantly greater in mining industries (15.7%, 95%CI 10.8-42.2), agriculture (11.1%, 2.3-19.8), and lower in commercial drivers (0.9%, 95%CI 0.1-2.4). Among the retrieved studies, 9 were based on laboratory analyses, 7 were questionnaire-based retrospective analyses, 5 were analyses of institutional databases. In 7 cases (all questionnaire bases), rather then benzodiazepine use, a proxy was reported (e.g. sedative, anxiolytics, etc). While no increased risk for occupational injuries was found among cross-sectional studies based on laboratory specimens (OR 0.59 95%CI 0.25-1.38; I2 63%), in questionnaire-based case control studies reporting the regular uptake of benzodiazepine was associated with higher risk for occupational injury (OR 2.11 95%CI 1.30-3.43, I2 55%). Conclusions: These results suggest an elevated risk of occupational injuries among individuals who have reported chronic use of benzodiazepines, while no actually increased use was reported from specimens associated with the occupational injury. Even though benzodiazepines have the potential to increase injury rates among chronic users, it is reasonable to understand the underline disorders (e.g. sleep deprivation, anxiety, etc) rather than benzodiazepine use per se as the actual risk factors to be specifically addressed. Key messages: Benzodiazepine use has the potential to increase the risk for occupational injuries, however evidence is conflicting. Underlying disorders causing the uptake of benzodiazepines rather than the drugs 'per se' are apparently associated with increased risk for occupational injuries.